The Ottoman Canon and the construction of Arabic and Turkish literatures - Arslan, C. Ceyhun (Edinburgh studies on the Ottoman Empire., 2024)
No detailed description available for ""The Ottoman Canon and the Construction of Arabic and Turkish Literatures"".